Role of gallbladder wall thickness in predicting laparoscopic operability prior to cholecystectomy: a retrospective analysis - Pathak, Priyank; Zaidi, Rihan (International Surgery Journal, 2018)
Background: Laparoscopic cholecystectomy is the gold standard procedure for cholecystitis. There are variable rates of conversion of laparoscopic cholecystectomy to open cholecystectomy. Various studies have highlighted gall bladder wall thickness of > 3mm as an independent risk factor for conversion. The purpose of our study is to predict the feasibility of cholecystectomy laparoscopically bases on the pre-operative ultrasound guided measurement of gall bladder wall thickness. Methods: It is a retrospective study conducted in the Department of Surgery, Himalayan Institute of Medical Sciences (HIMS) from June 2016 to September 2017. Patient’s pre-operative complete haemogram, liver function tests were also analyzed. Gallbladder wall thickness was estimated by using the maximal obtainable measurement at the fundus. A thin gallbladder wall was less than 3 mm in diameter. A thick gallbladder wall was 3 mm or greater in diameter. Results: A total of 192 patients were included in this study. Most of the patients were of the age group between 30-40 years, with average age of 37 years and 70% of the patients were females. Out of 192, 176 patients underwent laparoscopic cholecystectomy and 16 patients required conversion to open surgery. Ninety patients (46.8%) had cholecystectomy for acute cholecystitis and one hundred two patients (53.15%) had cholecystectomy for chronic cholecystitis. The gallbladder wall was found to be greater than 3 mm in 23 patients (25.5%) with acute calculous cholecystitis and greater than 3 mm in 25 patients (24.5%) with chronic calculous cholecystitis. Forty-eight patients, out of a total of 192, had a gallbladder wall thickness greater than 3 mm by preoperative sonography and 16 of these patients (33.3%) required conversion to an open cholecystectomy. Conclusions: Gall bladder wall thickness bases on ultrasound is a good predictor for difficult cholecystectomy and conversion to open surgery.